Analisis Sistem Manajemen Aset dalam Pengurusan Inventarisasi Dinas Ketenagakerjaan Kabupaten Pasuruan: Studi Digitalisasi Aset - Ayu Maulidyah, Tania DInda; Khumaidi, Khumaidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze digital asset management during the inventory process at the Pasuruan Regency Manpower Office to improve efficiency and accountability. The research method used is a descriptive qualitative approach, focusing on asset governance and the inhibiting factors in the implementation of a digital-based asset management system. The results show that the implementation of a digital system through SIDIA and E-Inventory supports real-time asset recording, verification, monitoring, and disposal, with an audit trail feature that strengthens transparency and accountability. Although obstacles remain related to reliance on physical documents and human resource adaptation. The study concludes that asset management at the Pasuruan Regency Manpower Office has transformed significantly toward an efficient and integrated digital system. However, the digitalization process is still in a transitional stage that requires continuous improvement. Keywords: Asset Management, Digital Inventory, SIDIA, E-Inventory, Government Digitalization